An ultrasonographic assessment to document the prevalence of various congenital uterine anomalies and their probable clinical outcome in the Eastern Uttar Pradesh region: A prospective study - Anamika Gaharwar; Priyanka Pandey; Navbir Pasricha; Eti Sthapak; Shamrendra Narayan (Wolters Kluwer Medknow Publications, 2022)
Background: Uterine anomalies arise from abnormal fusion of paramesonephric ducts or failure of apoptosis of septum between two ducts leading to abnormal division of the uterine cavity. Initial dearth of universal standard diagnosis was the reason for the improper reporting of the data associated with prevalence of uterine developmental anomalies. But now various authors have reported the prevalence of uterine anomalies using standard diagnostic techniques. The objective of the study was to assess the prevalence of various uterine congenital anomalies among women of reproductive age (15-45 years) with no previous uterine pathology. Methodology: An ultrasound was utilized to take a transabdominal sonographs of both longitudinal and transverse planes from the supine position of participants who were made to consume 500-1000 mL of water to promote diuresis for the duration of the scan. Scans were then interpreted. Results: From a study of 200 participants whose mean age group fell around 30 ± 8 years, 140 of the women were parous and 60 were nulliparous. Twelve of the participants displayed anomalies that included bicornuate, arcuate, and septate. Five cases of the bicornuate uterus (2.5%), four arcuate uterus (2.0%), and three septate uterus (1.5%) were noted. Conclusion: From a sample size of 200, the occurrence of uterine anomalies is 6%, with no cases of uterine agenesis or a hypoplastic uterus.